Orchestration of learning style differences and other variables in an action learning experience. - Robert L. Dilworth (Adult Education Research Conference, 1997)
Research centered on 31 students who participated in a two-week International Action Learning Seminar in Salford, England. International participants were assigned to action learning sets on the basis of several variables. Composition of sets (six to seven individuals) was purposely mixed to enhance diversity and promote learning.